Kebijakan Pelayanan Terpadu Satu Pintu di Kantor Kementerian Agama Kota Bengkulu - Bustari, Untung (JURNAL ILMIAH GEMA PERENCANA, 2025)
This study was prompted by initial findings from a community satisfaction survey, which indicated low service effectiveness as a crucial issue at the One-Stop Integrated Service (PTSP) office of the Ministry of Religious Affairs in Bengkulu City. The office still relies on a face-to-face system with limited waiting areas and special facilities. This study employs a qualitative methodology with analytical descriptive elements, where primary data was obtained from survey results, participant observation, documents, and archives. Secondary data was gathered from relevant laws and regulations, articles, journals, books, and reports concerning PTSP. The results show that although staff performance is excellent (Community Satisfaction Index score of 87.50), facilities (score of 68.33), processes (score of 70.20), and information environment (score of 72.00) remain low. The discussion reinforces that the inadequate physical conditions are due to suboptimal fund allocation, stemming from a lack of policy prioritization for infrastructure support. The conclusion emphasizes the need for significant transformation as existing policies are insufficient. Therefore, full digitalization of PTSP is recommended as the best policy alternative for revitalization, with a recommendation to the Ministry of Religious Affairs of Indonesia to create regulations for an accelerated revitalization and full digitalization program, committing to adequate fund allocation.